KEDUDUKAN AKTA PERJANJIAN PENGIKATAN JUAL BELI BERDASARKAN UTANG PIUTANG DITINJAU DARI ASAS PROPORSIONALITAS - Farida, Nur; Pratama, Febrian Rizki (Gapenas Publisher, 2024)
Nowadays, there are still many cases in the community about the practice of buying and selling land based on debt and credit, which causes unbalanced fulfillment of the rights and obligations of the parties who make it, and causes losses to one party, especially the party who transfers his land rights. Not infrequently there are also many Notary officials who are involved in the making of a sale and purchase binding agreement based on debt and credit, as in the example of a case decided by the Surabaya District Court with case number 198/Pdt.G/2019/PN.Sby. The purpose of this study is to determine the position of the deed of sale and purchase binding agreement based on debt and credit in terms of the principle of proportionality and to determine the role of notaries in protecting the interests of the rights and obligations of the parties to the agreement. The research method is normative juridical method using statute approach, and case approach. From the research it can be concluded that the position of the deed of sale and purchase binding agreement based on debt and credit is proven to violate the legal principle of proportionality and Notary as a public official has an important role in ensuring protection for the rights and obligations that may arise from agreements made by the parties involved.